Endothelial cells drive organ fibrosis in mice by inducing expression of the transcription factor SOX9 - Trogisch, Felix; Abouissa, Aya; Keles, Merve; Birke, Anne; Fuhrmann, Manuela; Dittrich, Gesine M.; Weinzierl, Nina; Wink, Elvira; Cordero, Julio; Elsherbiny, Adel; Martin Garrido, Abel; Grein, Steve; et al. (Science translational medicine, 2024)
Fibrosis is a hallmark of chronic disease. Although fibroblasts are involved, it is unclear to what extent endothelial cells also might contribute. We detected increased expression of the transcription factor Sox9 in endothelial cells in several different mouse fibrosis models. These models included systolic heart failure induced by pressure overload, diastolic heart failure induced by high-fat diet and nitric oxide synthase inhibition, pulmonary fibrosis induced by bleomycin treatment, and liver fibrosis due to a choline-deficient diet. We also observed up-regulation of endothelial SOX9 in cardiac tissue from patients with heart failure. To test whether SOX9 induction was sufficient to cause disease, we generated mice with endothelial cell-specific overexpression of Sox9, which promoted fibrosis in multiple organs and resulted in signs of heart failure. Endothelial Sox9 deletion prevented fibrosis and organ dysfunction in the two mouse models of heart failure as well as in the lung and liver fibrosis mouse models. Bulk and single-cell RNA sequencing of mouse endothelial cells across multiple vascular beds revealed that SOX9 induced extracellular matrix, growth factor, and inflammatory gene expression, leading to matrix deposition by endothelial cells. Moreover, mouse endothelial cells activated neighboring fibroblasts that then migrated and deposited matrix in response to SOX9, a process partly mediated by the secreted growth factor CCN2, a direct SOX9 target; endothelial cell-specific Sox9 deletion reversed these changes. These findings suggest a role for endothelial SOX9 as a fibrosis-promoting factor in different mouse organs during disease and imply that endothelial cells are an important regulator of fibrosis.